WHO AM I TO JUDGE? A REVIVAL OF THE PRIMACY OF CONSCIENCE AND THE IMPACT OF CULTURE IN THE FORMATION OF CONSCIENCE - Osuji, Peter I (Asian Horizons, 2016)
One of Pope Francis’ sayings that have resonated with many people is his response to the journalists on his flight back to Rome from Brazil on 29 July 2013. The Pope was asked about gay priests, homosexuals, and lesbians. His reply was “If someone is gay and he searches for the Lord and has good will, who am I to judge?” The pope has been advocating that the Catholic Church and her leaders adopt a less judgmental attitude in ministry, and particularly in moral teaching and practices. The Pope’s call is not only evident but is intensified in his recent Apostolic Exhortation Amoris Laetitia (The Joy of Love). I argue in this paper that the pope’s response is not only an amplification of the primacy of conscience doctrine but more importantly a clarion call to return to the doctrine of the primacy of conscience. It further denotes the need and the importance of culture in the formation of conscience.